Presentation - Gomez Matos, Mateo; Gonzales Pérez de Castro, Maricela; Lescano Feria, Patricia (Revista de Derecho, 2024)
This year marks the 40th anniversary of the Peruvian Civil Code, enacted in 1984, which has regulated legal relations in the country, promoting respect for fundamental rights and contributing to a fairer society. Throughout these four decades, the Code has been fundamental in the construction of Civil Law institutions, adapting to social changes and responding to new needs.In this context, the Faculty of Law of the University of Piura organised the First Legal Essay Competition with the aim of encouraging research and reflection on the impact of the Civil Code on today's society. The essays address technical and normative aspects of the Code, its relationship with other branches of law and its adaptation to contemporary social and technological realities, including proposals for reform.
Keywords: 40th anniversary; Peruvian Civil Code; reforms